Effects of carrageenin on human synovial cells in vitro: morphology, hyaluronic acid production, growth, and the lysosomal system. Issue 3 (June 1979) - Clarris, B J; Fraser, J R; Baxter, E; Malcolm, L P
Abstract : Some in-vitro effects of the arthritogenic polysaccharide carrageenin were studied on cells from human synovium. Synovial cells were isolated from intact human knee joints, and cell lines were developed by passaging with trypsin. Carrageenin was ingested by the cells but did not significantly affect cell growth, numbers of lysosomes, intracellular lysosomal enzyme activity (N-acetyl-beta-D-glucosaminidase), or release of lysosomal enzyme from cells. Carrageenin produced a reduction in net hyaluronic acid synthesis. It also induced a striking morphological change in a high proportion of synovial cells, characterised by increased spreading over the culture surface and apparent condensation of the cytoplasm into a pattern of ridges. Nonrheumatoid and rheumatoid synovial cells behaved similarly to one another.